Implementation of Structured Dyadic Methods to Improve Learning Results in Web and Mobile Device Programming Class XI Students in Software Engineering Expertise Program - Akbar, Nur Helmi (Universitas Pendidikan Indonesia, 2021)
This research is a Classroom Action Research (CAR) to 36 students of class XI RPL SMK Negeri 4 Bandung. This study aims to improve learning outcomes in the subjects of Web Programming and Mobile Devices for class XI RPL students of SMK Negeri 4 Bandung for the 2020/2021 academic year through the application of the Structured Dyadic Method. The data collection technique is done by using learning result test, observation and documentation. The data analysis technique used is descriptive quantitative data analysis with a percentage in the form of calculating the learning outcomes test and the observation results. The results of this classroom action research are 1) cognitive learning outcomes increase, in cycle I the average cognitive score of students is 51.25 or 22 students have reached KKM. In the second cycle the average cognitive score of students increased to 83.75 or 36 students had reached the KKM. 2) The learning outcomes of students' affective domains increased, in the first cycle as many as 22 students had reached the very good or good category and increased to 33 students in the second cycle. 3) The students' psychomotor learning outcomes increased, in the first cycle as many as 28 students had reached the very good or good category and increased in the second cycle to 33 students. Therefore, it can be concluded that the application of the Structured Dyadic Method learning method can improve learning outcomes in the cognitive, affective and psychomotor domains of class XI RPL SMK Negeri 4 Bandung Academic Year 2020/2021.